Analisis Risiko Kesehatan paparan Timbal pada Air Minum Masyarakat di Wilayah Eks Erupsi Sinabung Kecamatan Simpang Empat Karo - Khairunnisa Khairunnisa; Sri Malem Indirawati (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
The eruption of Mount Sinabung can cause pollution to the environment, especially raw water sources for drinking water and can cause health problems. The volcanic ash resulting from the eruption contains various kinds of minerals and heavy metals so that when the eruption occurs, volcanic ash can pollute the surrounding environment, including air, soil and water. Simpang Empat District is one of the districts affected by the eruption in Karo Regency. This study aims to determine the health risks due to exposure to lead in drinking water, the concentration of lead in drinking water and to analyze the characteristics of health risks due to exposure to lead in public drinking water. The research method used was descriptive survey research using a cross sectional approach. The research was conducted in Lingga Julu Village and was carried out from February to August 2020. Lingga Julu Village is one of the villages in Karo Regency which was affected by the eruption of Mount Sinabung and has a water source from a borehole which is managed by the local village government. The number of samples in this study were 47 respondents with a random sampling technique. The results showed that the lead concentration value was 0.0012 mg / l which was still below the environmental quality standard. The mean intake for real-time duration exposure was 0.00005 mg / kg / day with an RQ≤1 value of 0.013. Descriptively, intake of non-carcinogenic lead is not a risk to health. The estimated intake value for exposure to the next 50 years is 0.0024 with an RQ≤1 value of 0.6. Descriptively, intake of non-carcinogenic effect lead does not have a health risk for the people of Lingga Julu Village for the next 50 years. Keywords : Health risk analysis, lead, eruption, plumbum, intake